PENINGKATAN HASIL BELAJAR IPA MELALUI PENGGUNAAN METODE PEMBELAJARAN INQUIRY - salbiah . (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This study aims to determine the increase in student learning outcomes after science learning is applied to the material framework and the five human senses through the use of Inquire Learning Methods in fourth grade students of SD Negeri Julok Cut, East Aceh Regency. This type of research uses Classroom Action Research conducted in two cycles. The subjects of the study were 28 students in grade IV. The results showed that through the use of the Inquiry Learning Method, it turned out that student learning outcomes increased in each cycle. Mastery of the material in the initial conditions was still very low or had not been successful. Out of 28 students, only 9 students (32%) achieved the Minimum Completion Criteria (KKM) which was set at 70 with an average value of 60. From the research results it was revealed that in cycle I (one) the average value of students totaled 69, completeness learning reached 54%, the achievement of these values ​​showed an increase in the acquisition of values ​​in the initial conditions. While in cycle II (two) the average value of 77 students and completeness of learning reached 92%. The conclusion of this study was the use of the Instruction Method of Learning in the learning of science in the framework and five human senses material could have a positive effect on the improvement in learning outcomes of class IV semester II of the 2016-2017SD academic year. Negeri Julok Cut, East Aceh Regency.